Emerging treatment options for the management of pemphigus vulgaris - Kridin K (Dove Medical Press, 2018)
Khalaf Kridin Department of Dermatology, Rambam Health Care Campus, Haifa, Israel Abstract: Pemphigus vulgaris (PV) is a life-threatening disease belonging to the pemphigus group of autoimmune intra-epidermal bullous diseases of the skin and mucosae. The therapeutic management of PV remains challenging and, in some cases, conventional therapy is not adequate to induce clinical remission. The cornerstone of PV treatment remains systemic corticosteroids. Although very effective, long-term corticosteroid administration is characterized by substantial adverse effects. Corticosteroid-sparing adjuvant therapies have been employed in the treatment of PV, aiming to reduce the necessary cumulative dose of corticosteroids. Specifically, immunosuppressive agents such as azathioprine and mycophenolate mofetil are widely used in PV. More recently, high-dose intravenous immunoglobulins, immunoadsorption, and rituximab have been established as additional successful therapeutic options. This review covers both conventional and emerging therapies in PV. In addition, it sheds light on potential future treatment strategies for this disease. Keywords: azathioprine, meycophenolate mofetil, rituximab, intravenous immunoglobulins, immunoadsporption, emerging